2024
DOI: 10.1038/s41467-024-45247-6
|View full text |Cite
|
Sign up to set email alerts
|

The molecular interaction pattern of lenvatinib enables inhibition of wild-type or kinase-mutated FGFR2-driven cholangiocarcinoma

Stephan Spahn,
Fabian Kleinhenz,
Ekaterina Shevchenko
et al.

Abstract: Fibroblast growth factor receptor (FGFR)−2 can be inhibited by FGFR-selective or non-selective tyrosine kinase inhibitors (TKIs). Selective TKIs are approved for cholangiocarcinoma (CCA) with FGFR2 fusions; however, their application is limited by a characteristic pattern of adverse events or evocation of kinase domain mutations. A comprehensive characterization of a patient cohort treated with the non-selective TKI lenvatinib reveals promising efficacy in FGFR2-driven CCA. In a bed-to-bench approach, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In vitro experiments have provided evidence that lenvatinib effectively suppresses the proliferation signaling pathway of overexpressed VEGFR and FGFR in cancer cells [ 156 ]. Interestingly, lenvatinib offers a promising therapeutic option for FGFR 2-driven CCA, especially in cases involving insurmountable adverse effects to selective Tkis or acquired kinase mutations [ 157 ]. A Phase III clinical trial showed that lenvatinib was not inferior to sorafenib in patients with previously untreated advanced HCC (median survival time: 13.6 vs. 12.3 months), in contrast to sorafenib, lenvatinib exhibited substantial enhancements across all secondary endpoints, including a greater ORR, extended PFS, and increased time to progression (TTP) [ 158 ].…”
Section: Detection Of Fgfr Alterations In Tumorsmentioning
confidence: 99%
“…In vitro experiments have provided evidence that lenvatinib effectively suppresses the proliferation signaling pathway of overexpressed VEGFR and FGFR in cancer cells [ 156 ]. Interestingly, lenvatinib offers a promising therapeutic option for FGFR 2-driven CCA, especially in cases involving insurmountable adverse effects to selective Tkis or acquired kinase mutations [ 157 ]. A Phase III clinical trial showed that lenvatinib was not inferior to sorafenib in patients with previously untreated advanced HCC (median survival time: 13.6 vs. 12.3 months), in contrast to sorafenib, lenvatinib exhibited substantial enhancements across all secondary endpoints, including a greater ORR, extended PFS, and increased time to progression (TTP) [ 158 ].…”
Section: Detection Of Fgfr Alterations In Tumorsmentioning
confidence: 99%